MGT787: Change Management - UiTM, Faculty of Business Management (2023)
Organizations are continuously changing- those that do not plan for change and do not manage it strategically will fall behind. It is almost certain that every employee in every business will be affected by change initiative and where every manager will be an active player in the change process. A pervasive challenge for all organizations and their managers is how to initiate, implement and sustain major change. Change is everybody‘s responsibility and knowing how to plan for and implement and sustain change is a critical skill for every modern manager. This module discusses the need for change, assessing change options, planning for change and implementing and managing change process. Important sub-topics will be covered which include: overcoming resistance to change, diagnosing organization’s problems, becoming a change leader, and equipping employees to work in changed environment.